Influence of the target product on the electrochemical reduction of diluted CO2 in a continuous flow cell. (November 2022) - Van Daele, Sam; Hintjens, Lieven; Van den Hoek, Järi; Neukermans, Sander; Daems, Nick; Hereijgers, Jonas; Breugelmans, Tom
Abstract: To date, research on CO2 reduction is almost exclusively performed with pure CO2 while exhaust streams often contain low concentrations of CO2 . Direct usage of flue gases avoids the energy intensive CO2 capture step before utilization. This study compares the production of CO and formate on Ag and SnO2 catalysts respectively in order to find the most suitable target product for N2 -diluted feed streams. Initial product selectivity screening for different CO2 feed stream compositions was performed at 100 mA/cm 2 . Excessive hydrogen evolution emerged below 40 % CO2 for the silver catalyst while SnO2 maintained a Faradaic efficiency to formate > 70 % even at 10 % CO2 . Both catalysts were further tested at current densities up to 300 mA/cm 2 and show a shift of hydrogen evolution onset to more concentrated CO2 streams. These results indicate that formate production is more interesting when utilizing N2 -diluted CO2 feed streams compared to CO production. Graphical Abstract: ga1 Highlights: The importance of the target product and effect on the OH − balance is demonstrated. > 70 % Faradaic efficiency to formate for 10 % CO2 feed streams at 100 mA/cm 2 . Production of formate on SnO2 is less sensitive than CO on Ag for diluted CO2 feeds.